Characterization of the secondary structure of degummed Bombyx mori silk in modern and historical samples. (November 2018) - Badillo-Sanchez, Diego; Chelazzi, David; Giorgi, Rodorico; Cincinelli, Alessandra; Baglioni, Piero
Abstract: Understanding the degradation mechanisms of silk is essential for improving preventive conservation measures, and developing consolidation materials to restore the degraded fibers. Here, modern and historical silk samples were analyzed with an inclusive set of analytical techniques, in order to investigate the changes in the protein secondary structure that occurred upon natural aging or manufacturing processes. FTIR 2D Imaging-Chemical mapping allowed the non-invasive characterization of fibroin structure, and the obtained information was supported by Optical microscopy (OM), Scanning electron microscopy (SEM) and thermal analysis (Thermogravimetry, TGA, and Differential Scanning Calorimetry, DSC). Based on the acquired data, a different degradation stage was proposed for each historical sample, highlighting a heterogeneous conservation status. Highlights: First report on FPA FTIR 2D Imaging to inquire the secondary structure of fibrous silk fibroin, and changes induced by aging. The chemical imaging of the fibroin fibers allows characterizing the secondary structure distribution at the micron scale. A multi-analytical approach highlighted different degradation paths for fibroin, involving amorphous and crystalline domains.